Tuberous Sclerosis-A Case Report (International Journal of Biomedical Research, 2014)
A 18 yr old male patient presented with seizures. On thorough clinical evaluation and radiological investigation, he was diagnosed as a case of tuberous sclerosis. This case report emphasizes the importance of complete evaluation of a case presenting with seizures and inclusion of TSC (Tuberous Sclerosis Complex) as a differential diagnosis in children presenting with seizures, developmental delay and mental retardation.